Efisiensi Pengajaran Tafsir Al-Qur’an di Pondok Pesantren Raudlatul Hasaniyah Mojolegi Gading Probolinggo - Ahmad Khumaidi (Institut Ilmu Keislaman Zainul Hasan Genggong, 2016)
The Qur'an is the revelation of Allah. which was revealed to the Prophet Muhammad. which is believed to be a guide for us humans. The belief berkonitasi logical to put this book at a central position that is second to none in alignment to find clues Divine. Therefore an assessment of the scriptures remains attractive and actual anywhere and anytime. The assessment will be more interesting and very important, especially in a period in which Muslims with the full dynamics of life. At the boarding school Raudlatul Mojolegi Hasaniyah Probolinggo also contribute in order to strengthen the teaching of the Qur'an tafsir and Hifdzil. This kind of success can not be separated from teaching system of interpretation and methods that were applied dipondok schools specializing himself to teaching Tafsir and Tahfidz. From the data gathered in this study there are four learning methods of interpretation applied by clerics at boarding Raudlatul Hasaniyah Mojolegi Ivory Probolinggo, namely: (1) In the system of learning in the classroom; (A) lectures, (b) and answer method, (c) the method of discussion, and (d) the assignment method. (2) In a system of learning outside the classroom / cottage; (A) method shove, (b) the method bandongan, (b) the method of discussion / deliberation, and (d) the assignment method. The steps taken by clerics in the application of learning methods Tafsir, (1) In the system of learning in the classroom; (A) reading, (b) explain, (c) commissioned, and (d) evaluating. (2) In a system of learning outside the classroom / cottage; (A) pray / appetizer, (b) reading, (c) explain, (d) assigning, and (e) berdo'a / cover. Some of the constraints faced by clerics in the application of learning methods Tafsir Al-Qur'an at boarding Raudlatul Hasaniyah Mojolegi Ivory Probolinggo after analyzed lead to the educational background of religious scholars / teachers Tarsir Qur'an educated non-teacher, so that the application of the method interpretation of learning is imitation and basic consideration in the application of learning methods are not controlled. Although there are efforts in overcoming various constraints faced by clerics in the application of any type of learning method of interpretation among both the learning in the classroom and outside the classroom, but it is only theoretical in practice can not be done.